Oxidative stress and antioxidant enzyme activities in elite female Turkish cross-country skiers - Seyhan, S.; Bilici, M. F.; Demir, H.; Bilici, O. F.; Kahraman, M. Z.; Sahin, M. F.; Aglar, S.; Soylu, C.; Acar, G.; Kizilca, S. (BMC Sports Science, Medicine and Rehabilitation, 2026)
Background Oxidative stress-related processes contribute to exercise physiology through redox-sensitive signaling, yet when oxidant production exceeds antioxidant buffering, oxidative modifications may be reflected in circulating biomarkers. Evidence in elite female endurance athletes remains limited, particularly in cross-country skiers, and interpretation should be restricted to biomarker-level descriptions within the constraints of cross-sectional designs.